PUBLIC VALUE DALAM PENERAPAN LAYANAN ELECTRONIC RAFFIC LAW ENFORCEMENT (ETLE) DI KOTA SEMARANG - Salsabilla Nurul Nazhifa; Endang Larasati Setianingsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Electronic Traffic Law Enforcement (ETLE) is a technology-based traffic law enforcement system implemented by the Indonesian National Police to improve traffic order. The City of Semarang is one of the regions that has implemented ETLE as part of public service modernization. However, its implementation still faces several challenges, including the significant increase in motor vehicle ownership, persistently high traffic violation rates, uneven distribution of surveillance cameras, limited public outreach and understanding, and low levels of road user discipline. This study aims to analyze the public value of ETLE implementation in Semarang and to identify its supporting and inhibiting factors. The research employs a qualitative descriptive approach using in-depth interviews, observations, and documentation involving the Traffic Directorate of the Central Java Regional Police, the Traffic Unit of Semarang Metropolitan Police, and the community. The analysis is based on Public Value theory by Mark H. Moore (1995), which includes the dimensions of service, trust, and outcome, supported by public service quality theory by Moenir (2010). The results show that ETLE implementation has contributed positively to improving law enforcement effectiveness and public compliance, particularly in the outcome dimension. However, challenges remain in the service and trust dimensions, especially regarding infrastructure distribution, quality of information services, as well as transparency and public understanding. Supporting factors include staff awareness, organizational capacity, skills, and infrastructure, while regulatory aspects still require strengthening. This study recommends enhancing public outreach, information transparency, service quality, and infrastructure optimization to achieve more optimal public value.